الإعلام الجديد والتحولات الديمقراطية - عمر منصور, الدكتور : سليمان محمد (Sciences de l'Homme et de la Société, 2015)
صار للأعلام الجديد دورا هاما ورئيسا وفاعلا في سياق التحول الديمقراطي والإصلاح السياسي لدى بعض إفراد الشعب  في العديد من البلدان المختلفة ، مما أتاح فرصة كبيرة في تعزيز مشاركة الإفراد في النقاشات والحوارات إذ إنه وفر مساحة عامة لعامة الناس بدون استثناء مع رجال السياسة وصانعي القرار حول مختلف الإحداث والقضايا، وأصبح  شريكا رئيسيا في معظم حركات الاحتجاج الاجتماعي والسياسي في كل بلدان العالم ،كما قام الإعلام الجديد بدور كبير  لايستهان  به خلال ثورات الربيع العربي ، في إسقاط ثلاث أنظمة عربية ، ومع تطور تقنيات الإعلام الجديد أحدثت منفذ جديد للتعبير الحر دون رقابة، شخصية من احد ، وعززت من قيم  و حقوق الإنسان السياسية والاقتصادية والاجتماعية من خلال وسائله المتنوعة الحديثة ليصبح أكثر حضورا وانتشارا وفاعلية لعامة شرائح الشعب . Abstract:                                                                              New Media has become an important role and the president and actor in the context of democratization and political reform among some of the people in many different countries, which provided a great opportunity to promote the participation of individuals in the discussions and dialogues, as it provided a public space for the general public, without exception, with politicians and decision makers on various events and issues, and has become a major partner in the most social and political protest movements in all countries of the world, as the new media played a major role for the sizeable enough during the Arab Spring, in dropping three Arab regimes, with the development of new media technologies created a new outlet for free expression without censorship, personal of one, and reinforced the values and political, economic and social rights through the means of modern diversified to become more visible and widespread and effective for the general population segments..